2011
DOI: 10.1007/s13204-011-0048-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial potential of biosynthesised silver nanoparticles using Avicennia marina mangrove plant

Abstract: The present study was aimed to identify the antibacterial potential of biosynthesised silver nanoparticles using different plant parts (leaves, bark and root) of Avicenna marina mangrove plant. Of the selected three different parts, the leaf extract showed the maximum synthesis of silver nanoparticles. The in vitro antibacterial assay (100 lg disk-1 concentration) showed the results of maximum zone of inhibition with the E. coli (18.40 ± 0.97 mm), and minimum (10.87 ± 1.33 mm) zone of inhibition with S. aureus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(49 citation statements)
references
References 13 publications
2
47
0
Order By: Relevance
“…After the incubation period, the solution was centrifuged at 12,000 rpm for 20 min, and their pellets were re dispersed in Milli Q water. The centrifugation and redispersion was repeated three times to ensure the complete separation of nanoparticles (Gnanadesigan et al 2012). Later the pellets were air dried.…”
Section: Biosynthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…After the incubation period, the solution was centrifuged at 12,000 rpm for 20 min, and their pellets were re dispersed in Milli Q water. The centrifugation and redispersion was repeated three times to ensure the complete separation of nanoparticles (Gnanadesigan et al 2012). Later the pellets were air dried.…”
Section: Biosynthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…Our previous report demonstrated that silver nanoparticles can successfully be synthesized in a facile and cost-effective way using leaf extracts of Piper nigrum (Augustine et al 2014e). Biosynthesized silver nanoparticles were reported for their excellent antibacterial activity against wide range of microorganisms (Gnanadesigan et al 2012;Kathiraven et al 2014;Netala et al 2014;Sinha et al 2014;Kumar et al 2015;Kokila et al 2015;Roy et al 2014). Antifungal activity of biosynthesized silver nanoparticles is also well studied (Kumar et al 2013;Medda et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the plant-mediated synthesis of silver nanoparticles using Coleus aromaticus leaf (Vanaja and Annadurai 2013), living peanut seedling (Raju et al 2014), Petroselinum crispum leaf (Roy et al 2014), Citrus limon leaf (Vankar and Shukla 2012), Avicennia marina mangrove plant leaf, bark and root (Gnanadesigan et al 2012) and Justicia adhatoda L. Leaf (Bose and Chatterjee 2015) have been reported.…”
Section: Introductionmentioning
confidence: 99%